Development and reform of state housing programs in Ukraine. - Zeltser, Y. (Ways to Improve Construction Efficiency, 2023)
The need to provide the citizens of Ukraine with housing has become acute since Ukraine gained independence. The existing Soviet system of providing housing to citizens was broken, and the new system was never built. There are several categories of citizens who are legally entitled to free housing from the state. Also, some categories of citizens have the right to service apartments, which are provided to citizens temporarily. However, further privatization of such apartments in an automatic mode is not provided for by law. State housing programs provide assistance in obtaining housing for the rest of the citizens who do not have the right to receive housing free of charge. In 2020-2021, the Government of Ukraine and the National Bank of Ukraine did not implement the Presidential initiatives to significantly increase the volume of housing provision, including the introduction of effective mortgage and leasing financial instruments. Currently, state housing programs in Ukraine existed and exist only at the stage of pilot projects. Thus, according to the new state housing program "Homes in Action", in general, the state issued only 784 loans to Ukrainians in the amount of 1 billion 5.4 million hryvnias. In the period since the beginning of the full-scale war of russia against Ukraine, the problem of providing housing to citizens has become even more urgent. Damages from the destruction of the housing stock are estimated at $54 billion. In December, this amount increased by another $1.5 billion. Over ten months of war, a total of 149,300 residential buildings were damaged or destroyed. Thus, it is clearly premature to talk about the solution to the issue of housing for the citizens of Ukraine at the present time. It is clear that State housing programs in Ukraine need further development and reform. For this, first of all, institutional support for the development and reform of state housing programs in Ukraine is necessary, which is one of the leading and relevant directions of the development of modern economic science and practice. In order to solve this issue, it is necessary to complete a number of tasks listed in this article, which will make a significant contribution to the successful reform of state housing programs in Ukraine in the conditions of the country's reconstruction after the end of the full-scale war with russia..